Legitimasi Interpretasi Rasional antara Ibn Taymiyyah dan Ibn Rushd - Ahmad Najibul Firdaus; Abdul Kadir Riyadi (Jurnal Kawakib, 2025)
This study critically examines the contrasting perspectives of Ibn Taymiyyah and Ibn Rushd on the legitimacy of rational interpretation in Islam. Employing a qualitative method with comparative textual analysis, the research explores their methodologies, intellectual justifications, and critiques of opposing views. Ibn Taymiyyah advocates a literalist approach, emphasizing strict adherence to textual sources and rejecting allegorical interpretation (ta'wil), while Ibn Rushd harmonizes reason and revelation, endorsing ta'wil for philosophical inquiry. The findings highlight their epistemological divergences and convergences, offering insights into the historical dynamics of Islamic thought and the ongoing tension between textualism and rationalism. This study underscores the relevance of their debates in contemporary discussions on interpreting sacred texts.